Two new species of Western Australian Abantiades Herrich-Schäffer (Lepidoptera: Hepialidae) and a description of the female of Abantiades paradoxa (Tindale) - Moore, Michael D.; Beaver, Ethan P.; Bradford, Tessa; Hutchinson, Paul M.; Kay, Paul; Temby, Nick; Hamon, Howard; Stevens, Mark I. (Zootaxa, 2022)
Two new species, Abantiades concordia sp. nov. and Abantiades malleus sp. nov., are described from Australia. Both species were collected in the Eastern Goldfields subregion of the Coolgardie bioregion in Western Australia. Abantiades concordia sp. nov. is shown to be closely related to A. paradoxa (Tindale, 1932) by sequence similarity of the mtDNA (COI) gene. The female of A. paradoxa is also described here for the first time. Abantiades paradoxa and the new species A. concordia sp. nov. are morphologically similar with respect to the structure of their genitalia, sternite VIII, wing patterning and their antennae with bi-forked rami. Abantiades malleus sp. nov. is quite distinct by sequence similarity of the mtDNA (COI) gene, but related in a clade with A. marcidus Tindale,1932, A. albofasciatus (Swinhoe, 1892), and A. furva (Tindale,1932), the latter species once placed in the synonymised Bordaia Tindale, 1932. Discussion of similar species once grouped under the genus Bordaia and under the genus Trictena Meyrick, 1890 (both junior synonyms of Abantiades Herrich-Schäffer, 1855) is also included.